Negotiation Coordination Model for Supporting Enterprise Interoperability - Cretan, A.; Coutinho, C.; Bratu, B.; Jardim-Goncalves, R. (Enterprise Interoperability VII: Proceedings of the 8th International Conference on Interoperability for Enterprise Systems and Applications (I-ESA 2016), 2016)
The scientific evolution of negotiation in collaborative working environments allowed companies to benefit from new interoperability standards. The proliferation of SMEs led to a highly competitive environment, in which the various partners rely on interoperability and collaboration to be efficient. This paper highlights the role of negotiation in solving interoperability issues by proposing a distributive coordination model in order to manage multiple parallel negotiations. The research results will be validating within the European research project H2020 C2NET.